PENGARUH PENGGUNAAN MODEL PEMBELAJARAN INKUIRI TERBIMBING TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA DITINJAU DARI GAYA BELAJAR SISWA KELAS X SMA N KARANGPANDAN TAHUN PELAJARAN 2012/2013 - Agung Sularso; Puguh Karyanto; Bowo Sugiharto (Universitas Sebelas Maret, 2015)
The purpose of this study was to determine: 1) to determine the effect of the use of guided inquiry learning model in biology learning to critical thinking skills of class X SMA N Karangpandan academic year 2012/2013; 2) to determine the effect of learning styles of students to critical thinking skills class X SMA N Karangpandan academic year 2012/2013; 3) to determine the interaction between guided inquiry learning model with the learning styles of students' to critical thinking skills class X SMA N Karangpandan academic year 2012/2013.This study is a quasi-experimental research . Guided inquiry learning model was as independent variable, learning styles was as a moderate variable, and critical thinking skills was as the dependent variable. The study population was the entire class X SMA N Karangpandan first semester of the academic year 2012/2013. The sample was class X6 as control class and X3 grade students was as experiment class. The sampling technique used in this reserach was Cluster Random Sampling. Data collection techniques used critical thinking skills test technique while learning styles used questionnaire technique. Test the hypothesis using two-way Anava test and assisted by SPSS 20 with a significance level of 5%.Results from this research are: 1) The first hypothesis, based on two-way Anava test result was known that there is the influence of guided inquiry learning model to the critical thinking skills; 2) The second hypothesis, two-way ANOVA test result showed that learning styles do not affect the critical thinking skill; 3) The third hypothesis, the results of two-way ANOVA test showed that there was no interaction between guided inquiry learning model with learning style of the students to critical thinking skill.Based on the results of research the conclusions are: 1) guided inquiry learning model affects on students' critical thinking skills class X SMA Karangpandan 2012/2013 academic year, 2) the student's learning style does not give effect to the critical thinking skills class X SMA Karangpandan academic year 2012/20133) There is no interaction between guided inquiry learning model with the learning styles of students' to critical thinking skills class X SMA Karangpandan academic year 2012/2013. Keywords: Guided Inquiry Learning Model, Critical Thinking Skill, Learning Styles